Creep and Recovery Behavior of Compression Molded Low Density Polyethylene/Cellulose Composites. (18th December 2013) - Riara, Martin M.; Merenga, Abdallah S.; Migwi, Charles M.
Abstract : Low density polyethylene (LDPE) is an important industrial material because it is durable, light-weight, easily processed and characteristically inert, but its everyday use is hazardous to the environment. The solution to this seems to consist of incorporation of biopolymers in the structure of LDPE to form composites. Compression molded composites at different cellulose loading were subjected to creep tests at 30, 40, 50, and 60°C. The samples were displaced for 12 minutes and allowed to recover for 12 minutes. Creep behavior of the polymer composites was governed by temperature, time, and cellulose loading. Creep performance decreased with increase in temperature and improved with cellulose loading while creep modulus decreased with increase in time and temperature. Time temperature superposition was used to predict the long time (up to 10 6 s) creep behavior of the samples. William-Landel-Ferry (WLF) model offered a better description of the shift factors based on the short term data that was used to predict the long time behavior of the polymer composites by shifting the curves along the logarithmic time axis. The deformation was dependent on free volume.